Relationships of muscle quality and anthropometry with social determinants of health in noninstitutionalized elderly people (Research, Society and Development, 2025)
Social Determinants of Health (SDHs) have a substantial influence on the health status of the elderly population. During aging, there may be a reduction in muscle quality, which is directly related to loss of functionality and autonomy. The identification of aspects that associate poor muscle quality with SDHs in aging is reflected in possible personalized interventions to reduce this prevalence. This study aimed evaluate the relationships of muscle quality and anthropometric parameters with SDHs in elderly residents of a city in southern Minas Gerais. The sociodemographic and health conditions, income, education level, marital status, physical activity level, anthropometric measurements, bioelectrical impedance analysis (BIA), and hand grip strength were evaluated across 2 days to calculate the muscle quality index (MQI). Most of the study participants were women (82.6%), individuals aged 60 to 69 years (54.2%). Lower muscle quality was found in older elderly individuals (p=0.029), those who were less physically active (p=0.013), and those with lower education levels (p=0.037). The MQI was negatively correlated with age in years (ρ=-0.200, p=0.016) and Body Mass Index (BMI) (ρ=-0.182, p=0.029) and positively correlated with education level (ρ=0.172, p=0.049). The SDHs that showed the greatest association with muscle quality were age, physical activity level, education level, and BMI.